Romania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues and Statistical Appendix paper assesses Romania's external competitiveness by reviewing recent developments in a range of standard indicators and estimating equilibrium real exchange rates. The results suggest that, although Romania's historical cost advantage vis-a-vis trading partners has eroded since end-2004, on account of a strong real exchange rate appreciation, some undervaluation still remains. Furthermore, evidence suggests that the recent weak output and export performance in some of the traditional exporting sectors mainly reflects the transition toward higher value-added products.